2022
DOI: 10.3389/fnins.2022.1011824
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation improves swallowing initiation in patients with post-stroke dysphagia

Abstract: ObjectiveMore than half of post-stroke patients develop dysphagia, which manifests as delayed swallowing and is associated with a high risk of aspiration. In this study, we aimed to investigate the immediate effect of neuromuscular electrical stimulation (NMES) on swallowing initiation in post-stroke patients using videofluoroscopic swallowing study (VFSS) data.Materials and methodsThis randomized, self-controlled crossover study included 35 patients with post-stroke dysphagia. All selected patients received r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Among the 46 studies included, 29 studies ( 18 , 20 , 22 , 23 , 25 – 27 , 29 , 32 – 34 , 36 , 37 , 39 , 42 , 46 , 48 , 51 62 ) selected and reported appropriate randomization methods, such as random number table, so they were assessed as low risk of bias, the other 17 studies ( 19 , 21 , 24 , 28 , 30 , 31 , 35 , 38 , 40 , 41 , 43 – 45 , 47 , 49 , 50 , 63 ) only mentioned randomization allocation, so they were assessed as having the unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 46 studies included, 29 studies ( 18 , 20 , 22 , 23 , 25 – 27 , 29 , 32 – 34 , 36 , 37 , 39 , 42 , 46 , 48 , 51 62 ) selected and reported appropriate randomization methods, such as random number table, so they were assessed as low risk of bias, the other 17 studies ( 19 , 21 , 24 , 28 , 30 , 31 , 35 , 38 , 40 , 41 , 43 – 45 , 47 , 49 , 50 , 63 ) only mentioned randomization allocation, so they were assessed as having the unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 25 studies ( 18 , 22 , 25 – 27 , 29 , 31 , 33 , 35 , 37 , 39 , 46 , 51 63 ) reported the registration and ethical review of clinical RCTs, so the risk of bias was low. The remaining 21 studies were identified as having an unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional swallowing rehabilitation typically encompasses several components: (1) enhancement of the physical properties of food; (2) adjustment of eating position; (3) functional rehabilitation training for oropharyngeal and facial muscles, including sensory stimulation, oral and facial muscle strength training, coordination training for swallowing muscle movement, and swallowing skill training; (4) electrical stimulation of the pharyngeal muscles, including Neuromuscular Electrical stimulation (NMES), modified pharyngeal electrical stimulation (mPES) ( 7 ) and Pharyngeal electrical stimulation (PES) ( 6 , 8 , 11 ); (5) application of cold and hot stimulation to stimulate the pharyngeal mucosa; (6) Specific training for laryngeal elevation, hyoid muscle function, cricopharyngeal muscle function, pharyngeal cavity power, vocal cord function, and airway protection ( 11–13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, individuals with dysphagia following stroke often endure persistent swallowing difficulties, persisting up to six months post-onset ( 5 ). Neuromuscular Electrical stimulation (NMES), Pharyngeal electrical stimulation (PES) and modified Pharyngeal electrical stimulation (mPES), also have been reported as an effective treatment ( 6 , 7 ). Nevertheless, the exact mechanism of NMES, PES and mPES is unclear, and there has been little consensus on optimal electrode placement as well as proper frequency and intensity for stimulation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with brain injury-related dysphagia, the NMES strengthens both suprahyoid and infrahyoid muscles, along with the muscles that assist in swallowing ( Seo et al, 2021 ). Moreover, the long-term application of NMES benefits the recovery of swallowing-related cortical neuroplasticity in stroke patients ( Zhang et al, 2022 ). Given the loss of swallowing motor control in stroke patients, functional muscle contraction patterns are primarily re-educated during NMES ( Miller et al, 2022 ).…”
Section: Physical Therapymentioning
confidence: 99%